Vascular Disease in Patients with Nonalcoholic Fatty Liver Disease - Potze, Wilma; Siddiqui, M. Shadab; Sanyal, Arun J. (Seminars in Thrombosis and Hemostasis, 2015)
Nonalcoholic fatty liver disease (NAFLD) is increasingly being diagnosed and is considered to be the most frequent chronic liver disorder in Western countries. It represents a histopathological spectrum ranging from simple hepatic steatosis to steatohepatitis and finally cirrhosis. NAFLD is considered as the hepatic manifestation of the metabolic syndrome and is associated with increased mortality. Increasing evidence now suggests that NAFLD is also associated with higher cardiovascular disease (CVD) morbidity and mortality independent of conventional cardiometabolic risk factors (such as obesity, insulin resistance, and diabetes mellitus). The exact mechanisms linking NAFLD to increased CVD risk are still incompletely understood and likely reflect multiple coexisting pathways. Recent evidence suggests a contributive effect of an altered hemostasis in patients with NAFLD. For example, patients with NAFLD have higher levels of prothrombotic factors (e.g., von Willebrand factor, fibrinogen, factor VII activity, and plasminogen activator inhibitor-1), which correlate with underlying histological severity of the disease. The current review focuses on these hemostatic abnormalities in NAFLD and the link with increased CVD risk.
Keywords: nonalcoholic fatty liver disease; cardiovascular disease; hemostasis; coagulation disorders; thrombosis